Possibilities of new technologies in education. A review of interactive apps with developmental potential - Cackowska Małgorzata (Ars Educandi, 2013)
81Possibilities of new technologies in educationLiteratureBalicki M., 2005, Media a kompetencje kulturowe i społeczne dzieci [Media and children’s cul-tural and social competences] [in:] Dziecko i media elektroniczne. Nowy wymiar dzieciństwa, t. 1: Telewizja i inne mass media w życiu dziecka – wyzwaniem dla edukacji medialnej [The child and electronic media. A new childhood dimension, vol. 1: Television and other mass media in the child’s life – a challenge to media education], J. Izdebska, T. Sosnowski [eds.], Białystok: Wydawnictwo Trans Humana.Buckingham D., 2002, The Electronic Generation? Children and New Media [in:] Handbook of New Media, L. Lievrouw, S. Livingstone [eds.], London: Sage.Buckingham D., 2009, sec. ed., New media, new childhoods? Children’s changing cultural envi-ronment in the age of digital technology [in:] An introduction to childhood studies, M.J. Kehi-ly [ed.], Maidenhead, Berkshire: McGraw Hill/Open University Press.Cackowska M., 2013, Co ma książka obrazkowa do interaktywnej aplikacji książkowej? [What does a picturebook have to do with an interactive book app?], “Ryms” No. 20.Prensky M., 2001, Digital Natives, Digital Immigrants, “On the Horizon” Vol. 9, No. 5.Rideout V.J., 2014, Learning at home: Families’ educational media use in America. A report of the Families and Media Project, New York: The Joan Ganz Cooney Center at Sesame Workshop.SummaryPossibilities of New Technologies in Education. Overview of the Developmental Potential of Interactive AppsThe aim of the article is to highlight the educational and developmental role of apps for children. The text discusses the usefulness of apps and the role of interactivity in chil-dren’s development, both in family and school contexts. Apps are explored and described in different objective categories: creativity, special needs, maths, first concepts for toddlers and apps for preschoolers, app books. The article aims at turning the readers’ attention to the educational potential of the apps’ content.